Aperfeiçoamento experimental de um tubo de vórtice para acionamento por sistema solar fotovoltaico - Aragão, Thales Silva Ximenes de (2017)
The current work intends to focus in studying vortex tube with several configurations. Through it, one determines which parameters have to be studied in order to obtain the best thermodynamical performance. The main studied variations were the pressure - in a range from 1 to 6 bar - and the cold mass fraction, around 40%, as well as the number of inlets on the vortex chamber, 4 or 6. The best cold mass fraction were between 40 ans 50%. The performed analysis used a vortex device manufactured, which was working with a 7,5 hp compressor. Other instruments were used to obtain experimental data, like a device to measure the air flow, and several termocouples, which were monitoring the temperatures in the system. The experiments show a satisfactory coefficient of performance, which rates as high as 12%. The best configuration was a vortex pipe working at 6 bar and a 4 inlets vortex chamber. The exergy efficiency was studied and determined as well, with values of 2% in the best points. Those values presented only a little variation once the pressure was changed. With this analysis, this work performed the design and choice of solar panels, capable of feed the system. A paralel configuration of solar panes was defined, with 8 units working together.